NOWE TECHNOLOGIE A OBOWIĄZEK UJAWNIANIA DOKUMENTÓW I INFORMACJI PRZEZ SPÓŁKI W ŚWIETLE DYREKTYWY 2003/58/WE - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2017)
New Technologies and the Obligation to Disclose Documents and Particulars by Companies in the Light of Directive 2003/58/WE Summary Modern information and communication technology has a profound impact on our society. In particular, they have changed the way in which companies are functioning: the possible form of legal acts and of disclosure and filing of company information. So-called First Company Law Directive adopted in 1968 included provisions on a compulsory disclosure of documents and particulars. Since in the beginning of 21st century the compulsory disclosure system organised by the First Directive has become out-dated, the European Parliament and of the Council adopted Directive 2003/58/EC amending Council Directive 68/151/EEC, as regards disclosure requirements in respect of certain types of companies. In the article the provisions of the Directive 2003/58/EC are presented. Moreover, the author analyses what changes in the Polish Law will be necessary.